Front Cover: Improved Stability and Photodynamic Activity of Water‐Soluble 5, 15‐Diazaporphyrins Incorporated in β‐(1, 3‐1, 6)‐d‐Glucan with On‐Off Switch (Chem. Asian J. 3/2020). Issue 3 (21st January 2020) - Hino, Shodai; Satake, Shuhei; Shinmori, Hideyuki; Kawabata, Shigeki; Koumoto, Kazuya; Suzuki, Toshio; Nagasaki, Takeshi; Sugikawa, Kouta; Kawasaki, Riku; Ikeda, Atsushi
Abstract : Diazaporphyrins show a large absorption at wavelengths over 600 nm, which is the most suitable wavelength region for photodynamic therapy (PDT). Although aqueous solutions of 5, 15‐diazaporphyrins by complex formation with β‐(1, 3‐1, 6)‐D‐glucans are relatively stable, the β‐1, 3‐glucan‐complexed diazaporphyrins show weak fluorescence intensities and low singlet oxygen generation abilities due to self‐quenching. However, these complexes exhibit an "off‐state"‐to‐"on‐state" fluorescence switching activity upon intracellular uptake and show higher photodynamic activity toward HeLa cells under photoirradiation at long wavelengths (> 600 nm). More information can be found in the Full Paper by Atsushi Ikeda et al. on page 365 in Issue 3, 2020 (DOI: 10.1002/asia.201901582 ).